Robotic Process Automation in Small Enterprises: An Investigation into Application Potential - Sven Erdmann; Kurt Sandkuhl (Complex Systems Informatics and Modeling Quarterly, 2023)
Substantial application potential in enterprises is commonly attributed to Robotic Process Automation (RPA). This potential encompasses automation of routine tasks, improvement of data quality, improvement of process stability, or reduction of monotonous tasks. However, our observation from projects with enterprises is that this potential is visible in bigger companies, but not so obvious in small and medium-sized enterprises (SMEs). SMEs often show a lower readiness to invest time and resources in new technologies and, thus, hesitate to explore new technology applications unless they see a clear business case. This article investigates the application potential of RPA in SMEs by trying to identify typical application scenarios with potentially high benefits that SMEs should focus on. The application potential is primarily addressed from a qualitative perspective, i.e., the aim is not to quantify the potential but to qualify the application fields. The contributions of this article are (1) a structured literature review of the state of RPA use in SMEs, (2) RPA application scenarios visible in the literature and functionality of RPA platforms to support these scenarios, and (3) experiences from implementing three SME-focused use cases with off-the-shelf RPA tools and a concluding evaluation by experts.